Ayurveda Modalities in Palmoplanter Psoriasis-A Case Report - Trupti Thakre; Akshay Karemore; Sourabh Deshmukh (Journal of Pharmacy and Bioallied Sciences)
The non-inflammatory skin disorder known as palmoplantar psoriasis can potentially cause functional impairment. It is a specific type of psoriasis that only affects the palms and soles and includes symptoms like scaling, pustules, cracked skin, erythema, itching, and pain. All skin conditions are listed in Ayurveda under the heading (Kushtha) skin condition. It is compared to Vipadika Kshudra Kushta. Method: A male patient of age 9 years came with complaints of cracks over soles and palms with scaling for 1 year. The patient is treated by Shaman Chikitsa like Avipattikarchurna, Haridra Khanda, Gandhakrasayan, Arogyavardhinivati, Karanja taila, and Padchira ointment for 2 months. Result: The cracks which were present over soles and palm are reduced by Shaman Chikitsa. Conclusion: Thus, it can be said that topical cream application along with oral medication can be treat palmoplantar psoriasis.